2021
DOI: 10.1002/adfm.202102713
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Healing Cs3Bi2Br3I6 Perovskite Wafers for X‐Ray Detection

Abstract: Self-healing of defects imposed by external stimuli such as high energy radiation is a possibility to sustain the operational lifetime of electronic devices such as radiation detectors. Cs 3 Bi 2 Br 3 I 6 polycrystalline wafers are introduced here as novel X-ray detector material, which not only guarantees a high X-ray stopping power due to its composition with elements with high atomic numbers, but also outperforms other Bi-based semiconductors in respect to detector parameters such as detection limit, transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Furthermore, the mt product was also estimated by fitting the current response under X-ray photons and found to be 1.08 Â 10 À4 cm 2 V À1 (seen in Fig. S3, ESI †), which is comparable to the values of most low-dimensional perovskite single crystals and polycrystals 3,44,45 (e.g., 4.43 Â 10 À4 cm 2 V À1 for the (BDA)PbI 4 single crystal, 42 5.1 Â 10 À4 cm 2 V À1 for the (F-PEA) 2 PbI 4 single crystal, 48 2 Â 10 À4 cm 2 V À1 for the MAPbI 3 wafer, 12 4.6 Â 10 À5 cm 2 V À1 for the MA 3 Bi 2 I 9 wafer, 22 3.6 Â 10 À5 cm 2 V À1 for the Cs 3 Bi 2 Br 3 I 6 wafer, 49 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the mt product was also estimated by fitting the current response under X-ray photons and found to be 1.08 Â 10 À4 cm 2 V À1 (seen in Fig. S3, ESI †), which is comparable to the values of most low-dimensional perovskite single crystals and polycrystals 3,44,45 (e.g., 4.43 Â 10 À4 cm 2 V À1 for the (BDA)PbI 4 single crystal, 42 5.1 Â 10 À4 cm 2 V À1 for the (F-PEA) 2 PbI 4 single crystal, 48 2 Â 10 À4 cm 2 V À1 for the MAPbI 3 wafer, 12 4.6 Â 10 À5 cm 2 V À1 for the MA 3 Bi 2 I 9 wafer, 22 3.6 Â 10 À5 cm 2 V À1 for the Cs 3 Bi 2 Br 3 I 6 wafer, 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…S3, ESI†), which is comparable to the values of most low-dimensional perovskite single crystals and polycrystals 3,44,45 ( e.g. , 4.43 × 10 −4 cm 2 V −1 for the (BDA)PbI 4 single crystal, 42 5.1 × 10 −4 cm 2 V −1 for the (F-PEA) 2 PbI 4 single crystal, 48 2 × 10 −4 cm 2 V −1 for the MAPbI 3 wafer, 12 4.6 × 10 −5 cm 2 V −1 for the MA 3 Bi 2 I 9 wafer, 22 3.6 × 10 −5 cm 2 V −1 for the Cs 3 Bi 2 Br 3 I 6 wafer, 49 and 8.5 × 10 −5 cm 2 V −1 for Cs 2 AgBiBr 6 /(C 38 H 34 P 2 )MnBr 4 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…To address this issue, solution-processed perovskite micro-crystals/powders are often employed as starting structures to be pressed for the fabrication of thick films and wafers. 7 b ,16 In 2017, Shrestha et al reported on high-performance direct X-ray detectors based on sintered MAPbI 3 perovskite wafers (Fig. 2d).…”
Section: Processing Of Perovskite Thick-junctionsmentioning
confidence: 99%
“…It should be emphasized that large on-off ratio is 161 an important parameter for an X-ray detector. [26] Because if 162 the detector has an ideal on-off ratio, but the photocurrent is 163 too small for the external readout circuit to achieve efficient 164 collection, the signal can simply be amplified by an external 165 amplifier. In contrast, this method appears to be infeasible if 166 the device has a poor on-off ratio.…”
mentioning
confidence: 99%